(untitled) (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2025)
CONTEXTUALIZAÇÃO: Long COVID often involves neurological and musculoskeletal complications, which can affect quality of life and work capacity. However, the long-term impact of COVID-19 on neuromuscular function and muscle architecture of the lower limbs in COVID-19 survivors is still unclear. OBJETIVOS: To evaluate neuromuscular electrophysiological disorders (NEDs) and the muscle architecture of the tibialis anterior (TA) and triceps surae (TS) muscles in individuals who had moderate or severe COVID-19, in comparison with a healthy control group, over a 12-month period. MÉTODOS: This Level 2 longitudinal study was approved by the Research Ethics Committee of the University of Brasília (CAAE 45043821.0.0000.8093) and conducted according to the ethical standards of the Declaration of Helsinki. Seventy participants were selected and divided into three groups: moderate COVID (n=22), severe COVID (n=18), and control (n=30). Four assessments were conducted for the groups that had COVID-19 over the course of one year. Neuromuscular electrophysiological disorders (NEDs) in the tibialis anterior (TA) and lateral gastrocnemius (GL) muscles were evaluated through the electrodiagnostic stimulation test, while the muscle architecture of the TA and triceps surae (TS) muscles was analyzed using ultrasound imaging. RESULTADOS: Participants who had severe COVID showed significantly higher chronaxia values (p<0.001) in the tibialis anterior (TA) muscle during the first assessment, compared to the moderate COVID and control groups. In the severe COVID group, neuromuscular electrophysiological disorders (NEDs) were observed in the TA muscle in 55.55%, 33.33%, and 16.66% of participants in the first three assessments, respectively. In contrast, the lateral gastrocnemius (GL) muscle showed only a 5.55% prevalence of NEDs in the same group. Regarding the muscle architecture analysis, over the 12 months, echogenicity consistently increased in the TA and GL muscles in the severe COVID group (p<0.001), a phenomenon not observed in the other evaluated groups. Additionally, there was a significant association between the chronaxia values of the TA and echogenicity in the COVID groups during the short-term assessment (p<0.001). CONCLUSÕES: Severe COVID-19 is associated with a higher prevalence of NEDs in the TA muscle and persistent increases in echogenicity in all muscles, suggesting acquired polyneuromyopathy in the TA and generalized echogenicity abnormalities in patients with long COVID. IMPLICAÇÕES: Patients with long COVID may experience persistent neuromuscular disorders over time. Severe COVID-19 is linked to neuromuscular dysfunctions even after 12 months. In this context, it is essential for physiotherapists to include neuromuscular rehabilitation as a key component in the treatment of patients with long COVID.